Transcriptomic Deconvolution in Acute Myocardial Infarction: Exploring Diagnostic Potential and Validation Through Blood Counts - Murilo de Queiroz Ramos; José Victor Almeida Guimarães; Diego Moura Tanajura; Kiyoshi Ferreira Fukutani; Hanjia Gao (Cardiology Discovery)
Abstract. Objective:. This study aimed to evaluate the immune cell populations in patients with acute myocardial infarction (AMI). Methods:. The keyword “myocardial infarction” was searched in the Gene Expression Omnibus database, and only transcriptomes from peripheral blood studies of patients with AMI within 12 h of symptom onset were included. Patients without myocardial infarction from the same database were included in the control group. The differential analysis of expressed genes, the enrichment of metabolic pathways associated with the significant genes, and the proportions and absolute values of immune cells between 2 groups (AMI and control) were analyzed. To validate the findings, neutrophil and lymphocyte counts were obtained from blood counts and correlated with creatine kinase-MB levels in 22 patients with AMI from Hospital Geral Roberto Santos. Results:. Two microarray datasets from the Gene Expression Omnibus database were analyzed, containing a total of 31 eligible blood transcriptome samples. These samples included 14 patients with AMI and 17 non-infarcted patients (control group). Patients with AMI showed significant gene expression differences compared to the control group (P < 0.05). The enrichment analysis of the significant genes revealed an association with immune cells. The proportions of cell populations in patients with AMI from both datasets revealed an increase in neutrophils and a decrease in T and B lymphocytes, which were statistically significant (P = 0.018, P = 0.047, respectively). The analysis of absolute cell numbers demonstrated higher neutrophil values and lower T cell values in patients with AMI compared to the control group (all P < 0.05 in GSE61144 and GSE60993 datasets). The data from Hospital Geral Roberto Santos showed that the percentage of neutrophils showed a positive correlation (r = 0.5, P = 0.018), while the percentage of lymphocytes showed a negative correlation (r = –0.45, P = 0.034) with creatine kinase-MB levels in patients with AMI. Conclusion:. This study suggests that data derived from differential cell counts could serve as an additional parameter to diagnose AMI. Neutrophilia and lymphopenia in AMI should not be used as isolated parameters, but they indicate the need for further investigation, particularly in patients with uncertain diagnoses.